Structure‐Guided Design of G‐Protein‐Coupled Receptor Polypharmacology. Issue 33 (16th July 2021) - Kampen, Stefanie; Duy Vo, Duc; Zhang, Xiaoqun; Panel, Nicolas; Yang, Yunting; Jaiteh, Mariama; Matricon, Pierre; Svenningsson, Per; Brea, Jose; Loza, Maria Isabel; Kihlberg, Jan; Carlsson, Jens
Abstract: Many diseases are polygenic and can only be treated efficiently with drugs that modulate multiple targets. However, rational design of compounds with multi‐target profiles is rarely pursued because it is considered too difficult, in particular if the drug must enter the central nervous system. Here, a structure‐based strategy to identify dual‐target ligands of G‐protein‐coupled receptors is presented. We use this approach to design compounds that both antagonize the A2A adenosine receptor and activate the D2 dopamine receptor, which have excellent potential as antiparkinson drugs. Atomic resolution models of the receptors guided generation of a chemical library with compounds designed to occupy orthosteric and secondary binding pockets in both targets. Structure‐based virtual screens identified ten compounds, of which three had affinity for both targets. One of these scaffolds was optimized to nanomolar dual‐target activity and showed the predicted pharmacodynamic effect in a rat model of Parkinsonism. Abstract : Structure‐based modelling was used to design a single compound with the ability to modulate the activity of two G‐protein‐coupled receptors relevant for Parkinson's disease. The most potent scaffold displayed nanomolar binding affinities for both targets and was active in a rat model of parkinsonism.